الضمانات الدستورية والقانونية للمتهم الواجب توفرها في مرحلة المحاكمة - Tarek, Mohammad; Mahmoud Mohamed Ali Mahmoud Edris; Ahmad Syukran Baharuddin (Intelligentia Resources is an open-ac, 2024)
Vol. 1 No. 1 (2022) (page 75-101)